2011
DOI: 10.3989/egeol.40393.205
|View full text |Cite
|
Sign up to set email alerts
|

<i>Morotochoerus</i> de Uganda (17.5 Ma) y <i>Kenyapotamus</i> de Kenia (13-11 Ma): implicaciones sobre el origen de los hipopotámidos

Abstract: The aim of this paper is to describe and interpret suiform teeth from Moroto, Uganda, and Ngorora, Kenya, which contribute to the debate about hippo-anthracothere-whale relationships. The early stages of hippopotamid evolution are relatively poorly known on account of the paucity of their fossil record older than 7 Ma. New specimens of Morotochoerus from Uganda reveal that it is not closely related to Hippopotamidae; the superficial resemblances of the cheek teeth to those of hippos represent convergences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The common hippo, Hippopotamus amphibious Linnaeus, 1758, and the pygmy hippo, Choeropsis liberiensis Leidy, 1852, are the only two representatives of extant hippopotamids that would have diverged from each other at about 5.7 Mya (Montgelard et al, 1997). Whereas hippopotamids may have originated in the Early Miocene, Orliac et al (2010) considered an origin at about 21 Mya, while Pickford (2011) argued for their first appearance at about 16.5 Mya. Regardless of the exact timing of their origin, hippopotamids may have adopted semi-aquatic habits at least as early as the latest Miocene (Boisserie et al, 2011).…”
Section: Origin and Evolution Of Chelonian Polystomesmentioning
confidence: 93%
“…The common hippo, Hippopotamus amphibious Linnaeus, 1758, and the pygmy hippo, Choeropsis liberiensis Leidy, 1852, are the only two representatives of extant hippopotamids that would have diverged from each other at about 5.7 Mya (Montgelard et al, 1997). Whereas hippopotamids may have originated in the Early Miocene, Orliac et al (2010) considered an origin at about 21 Mya, while Pickford (2011) argued for their first appearance at about 16.5 Mya. Regardless of the exact timing of their origin, hippopotamids may have adopted semi-aquatic habits at least as early as the latest Miocene (Boisserie et al, 2011).…”
Section: Origin and Evolution Of Chelonian Polystomesmentioning
confidence: 93%
“…Apparently, these uncertainties sustained a diversity of opinions on the affinities of Hippopotamidae within fossil cetartiodactyls (for example, refs [2][3][4][5][6][7][8]. Among these, some noncladistic approaches are still radically in disagreement with molecular data 7,8 , whereas combined data set analyses have essentially maintained an unclear emergence of Hippopotamidae from an Oligocene ghost lineage, for example refs 3,4,9. In fact, the integration of Miocene hippopotamid data into morphology-based cladistic analyses brought substantial support to a hippopotamid emergence among anthracotheres 10,11 .…”
mentioning
confidence: 99%
“…Among these, some noncladistic approaches are still radically in disagreement with molecular data 7,8 , whereas combined data set analyses have essentially maintained an unclear emergence of Hippopotamidae from an Oligocene ghost lineage, for example refs 3,4,9. In fact, the integration of Miocene hippopotamid data into morphology-based cladistic analyses brought substantial support to a hippopotamid emergence among anthracotheres 10,11 . However, this approach did not succeed in precisely identifying the stem group of Hippopotamidae among anthracotheres.…”
mentioning
confidence: 99%
“…Tsubamoto et al (2011) also suggested a possible hippopotamid affinity of Kulutherium. In contrast, Pickford (2011) suggested an anthracotheriid affinity of Morotochoerus and Kulutherium. However, the fossil material of these two early Miocene genera is very limited (Pickford, 1998(Pickford, , 2007a.…”
Section: Introductionmentioning
confidence: 87%
“…Pickford, 2007bPickford, , 2008Pickford, , 2011Boisserie and Lihoreau, 2006;Boisserie et al, 2010Boisserie et al, , 2011Tsubamoto et al, 2011;Alloing-Séguier et al, 2014;Lihoreau et al, 2015; and references cited therein). The undoubtedly oldest record of the family is from the middle Miocene of Kenya, which has yielded a kenyapotamine hippopotamid, Palaeopotamus ternani (= Kenyapotamus ternani) (Pickford, 1983(Pickford, , 2007b(Pickford, , 2008(Pickford, , 2011Boisserie and Lihoreau, 2006;Boisserie, 2007;Boisserie et al, 2010;Weston and Boisserie, 2010). A few years ago, Orliac et al (2010) suggested that Morotochoerus from the lower Miocene of Uganda and Kulutherium from the lower Miocene of Kenya were representatives of primitive hippopotamids and tentatively assigned them to the Kenyapotaminae.…”
Section: Introductionmentioning
confidence: 99%